When did we see you naked?: Jesus as a victim of sexual abuse - Reaves, Jayme R.; Tombs, David; Figueroa, Rocio (SCM Press, 2021)
Was the stripping and exposure of Jesus a form of sexual abuse? If so, why does such a reading of Jesus' suffering matter? The combined impact of the #MeToo movement and a further wave of global revelations on church sexual abuse have given renewed significance to recent work naming Jesus as a victim of sexual abuse. Timely and provocative When Did We See You Naked? presents the arguments for reading Christ as an abuse victim, as well as exploring how the position might be critiqued, and what implications and applications it might offer to the Church. The collection includes an impressively diverse international field of contributors drawn from a range of disciplines